1995
DOI: 10.1007/bf02248767
|View full text |Cite
|
Sign up to set email alerts
|

Fatalism as a barrier to cancer screening among African-Americans: Philosophical perspectives

Abstract: Fatalism has been identified as a crucial barrier to participation in cancer screening among African Americans. The essence of fatalism is woven throughout the lived experience for some African Americans. Therefore, to fully understand its impact, fatalism must be viewed within its broadest historical and sociocultural context. This article explores the philosophical origins and the practical significance of fatalism with regard to cancer screening among this population. Health care professionals must position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 5 publications
2
57
1
Order By: Relevance
“…Our results are consistent with the argument that racial/ethnic differences in fatalistic beliefs about cancer prevention may be attributable to differences in socioeconomic status (9,10), although the finding that Spanish-speaking Hispanic respondents were more likely to hold at least one fatalistic belief about prevention than Whites suggests that ethnicity and culture do play a role in cultivating these beliefs (16). Fatalism about cancer survivorship may nevertheless have stronger ethnic and cultural origins (12,13,25). Future studies, particularly those using longitudinal panel designs, would help to draw stronger conclusions about the relationship between race/ethnicity, education, and cancer fatalism.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our results are consistent with the argument that racial/ethnic differences in fatalistic beliefs about cancer prevention may be attributable to differences in socioeconomic status (9,10), although the finding that Spanish-speaking Hispanic respondents were more likely to hold at least one fatalistic belief about prevention than Whites suggests that ethnicity and culture do play a role in cultivating these beliefs (16). Fatalism about cancer survivorship may nevertheless have stronger ethnic and cultural origins (12,13,25). Future studies, particularly those using longitudinal panel designs, would help to draw stronger conclusions about the relationship between race/ethnicity, education, and cancer fatalism.…”
Section: Discussionsupporting
confidence: 87%
“…''; refs. 7,10,15,[23][24][25]. Each item was measured with a five-point Likert scale with response categories ranging from strongly disagree to strongly agree.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors support previous researchers by pointing out the fact that research on the construct of cancer fatalism among persons diagnosed with cancer is sparse, as much of the research on this topic has focused on noncancer participants and the influence of cancer fatalism on screening behaviors [1][2][3][4][5][6][7][8][9][10]. Findings from this study raise the question of whether the philosophical underpinnings of fatalism, as it relates to screening, change or are perhaps different once an individual becomes a survivor.…”
supporting
confidence: 53%
“…Findings from this study raise the question of whether the philosophical underpinnings of fatalism, as it relates to screening, change or are perhaps different once an individual becomes a survivor. It has been shown that perceptions of cancer fatalism are not an "all or none phenomenon" and in fact, it may be the strength of these perceptions that influenced screening behaviors as opposed to their presence or absence [8].…”
mentioning
confidence: 99%